2016
DOI: 10.1177/1748895816642502
|View full text |Cite
|
Sign up to set email alerts
|

An intersectional approach to race/ethnicity, sex, and age disparity in federal sentencing outcomes: An examination of policy across time periods

Abstract: Approaches to intersectionality stress the importance of recognizing multiple, intersecting inequalities. As such, recent sentencing research has examined the changing role of extra-legal characteristics on United States federal sentencing outcomes in the aftermath of recent policy changes (e.g. United States v. Booker), but scholarship has less often examined these characteristics at the intersections of race/ethnicity, gender, and, especially age. This article uses an intersectional approach to examine the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…A large body of research has examined differences in the types of sentences meted out to men and women. Broadly, the results indicate that women benefit from leniency at the sentencing stage (Belknap, 2007;Daly & Bordt, 1995;Doerner & Demuth, 2014;Nowacki, 2017). This individual-level disparity is generally explained through the focal concerns (Steffensmeier et al, 1993;Steffensmeier et al, 1998), judicial paternalism (Daly, 1989;Moulds, 1980), and selective chivalry (Farnworth & Teske, 1995) perspectives.…”
Section: Gender Disparity In Sentencingmentioning
confidence: 95%
“…A large body of research has examined differences in the types of sentences meted out to men and women. Broadly, the results indicate that women benefit from leniency at the sentencing stage (Belknap, 2007;Daly & Bordt, 1995;Doerner & Demuth, 2014;Nowacki, 2017). This individual-level disparity is generally explained through the focal concerns (Steffensmeier et al, 1993;Steffensmeier et al, 1998), judicial paternalism (Daly, 1989;Moulds, 1980), and selective chivalry (Farnworth & Teske, 1995) perspectives.…”
Section: Gender Disparity In Sentencingmentioning
confidence: 95%
“…Sex-specific analysis is important in this regard for several reasons. First, comparisons between men and women often assume that there is a universal experience shared by all women and that oppression and marginalization do not differ across varying social characteristics (Nowacki, 2017).…”
mentioning
confidence: 99%
“…Using aggregated federal sentencing data from 2000 to 2002, the authors note that being Black or Hispanic is related to an increased sentence length for both sexes, jointly and independently. Likewise, in a study examining federal sentencing data from 1999 to 2008, Nowacki (2017) found that White women receive the most lenient sentence lengths while Hispanic women receive the most severe outcomes. Sentencing outcomes for Black women fell somewhere in the middle.…”
Section: Sentencing Disparities Among Womenmentioning
confidence: 99%
“…Extralegal correlates of sentencing outcomes are also included. As previous research has found age and education to be relevant (Doerner & Demuth, 2010;Nowacki, 2017;Steffensmeier et al, 2017), this study controls for both measures. Age is included as a numeric value; no transformations were necessary as this variable was not found to be skewed.…”
Section: Level 1 Variablesmentioning
confidence: 99%